BIMBINGAN KONSELING ISLAM DENGAN TERAPI BEHAVIOR UNTUK MENANGANI ADIKSI MEROKOK PELAJAR SD (Jurnal Bimbingan dan Konseling Islam, 2014)
The focus of this study were (1) How is the Islamic Guidance andCounseling with Behavior Therapy in dealing with the addiction of smoking anelementary school in the village of Pangkahkulon Ujungpangkah Gresik ?; and(2) How do the results of guidance and counseling Islam with BehaviorTherapy in dealing with the addiction of smoking an elementary school in the village of Pangkahkulon Ujungpangkah Gresik ?. This study uses descriptivequalitative comparative analysis. The analysis is based on interviews and observations. This research was conducted through behavior therapy withmodeling techniques. Mechanical modeling is done by using symbolic modelsand real models. Modeling techniques performed while observation by adding and subtracting the observed behavior. The purpose of this therapy is to eliminate poor behavior towards better. Haasil the end of the process ofcounseling to clients in this study was quite successful with a percentage of75%. These results can be seen from the change in clients who had not smokedagain and changes in behavior on the client's self after receiving guidance andcounseling provided by counselors Islam.